دلالات التشبيهات القرانية بناء علي المشبهبه : دراسة تحليلية - Qaziah Fatihah binti Berhanuddin (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This research aims at three matters; to classify the modes of Mushabbah Bih of theQur'ānic similes by the significance of their physical aspects, to study the semantic research of the Qur'ānic similes done by the scholars over the years, and essentially to present the new semantics into this field which are derived from the modes of Mushabbah Bih. In order to accomplish these aims, the research was carried out by following the deductive, analytical, and extractive methodologies. As a prelude to the discussion of this research, the researcher exposes in Chapter One the meaning of simile and its' components, in which it talks about the historical emergence, the complete definitions, the pillars, and the categorizations of simile. In Chapter Two, the researcher focuses on some of the previous studies of the Qur'ānic similes, and at the same time suggests the new classifications of the modes of Mushabbah Bih regarding their physical aspects. Meanwhile in Chapter Three, the researcher brings out the domains of semantical studies of the Qur'ānic similes in two inspections; firstly focusing on the discussion of the researches by several scholars from different fields about this topic, and secondly, advancing the identical performance by the researcher while discussing and suggesting the brand-new semantics for the animal mode of Mushabbah Bih analytically in the eight Qur'ānic verses. Finally, others would see that the result of this research indicates the essential modes of Mushabbah Bih through the semantical approach that has the direct link with a specific way by any selected field of researcher. Nonetheless, this essential element will become the fundamental part to be acquired by the researchers in sequence to come out with another proposition of semantics of the Qur'ānic similes, in which it leads them to deeply understand the rhetorical declaration and inimitability of the Qur'ānic similes.